Eco-Engineering for Managing Insect Pests in Rice Fields - Bari, M N; Haque, S S; Nowrin, F; Ali, M P; Kabir, M M M; Akter, S; Roy, T K; Afrin, S (Bangladesh Rice Journal, 2025)
This study was consisted of eight experiments across Boro and Transplanted Aman seasons in various locations in Bangladesh to explore eco-friendly insect pest control methods in rice fields. The primary objectives were to safeguard natural-enemies through ecological engineering techniques and minimize the use of insecticides in rice farming. Ecological engineering aimed to boost biodiversity in the rice environment, fostering both plant and animal diversity to offer extra support for natural enemies in terms of sustenance and shelter. To fulfill these objectives, nectar-rich flowering plants such as marigold, cosmos, sesame and sunflower were planted strategically in rice bunds ensuring habitats by establishing crucial sources of food and protection for beneficial insects. These beneficial insects, in turn, contribute to biological pest control by establishing an equilibrium between harmful and beneficial insects within the rice ecosystem and consequently reducing the dependency on insecticides. The study consisted of two treatments, T1: Rice fields with flowering plants on bunds; and T2: Farmer's practice of prophylactic insecticide use. The study observed a significant increase in the predators and parasitoids abundance in eco-engineering field (T1) compared to insecticide-treated fields (T2). Across seasons and locations, T1 consistently showed higher populations of various beneficial insects such as spiders, damsel flies, dragon flies, ladybird beetles, carabid beetles, staphylinid beetles, green mirid bugs, and parasitic wasps compared to T2. Notably, despite maintaining insect infestation below the economic threshold level in both T1 and T2, T1 exhibited significantly higher egg parasitism rates of rice hispa, brown planthopper, yellow stem borer, and rice leafroller compared to T2. Remarkably, on an average while achieved statistically similar yields between T1 and T2 (5.99 t/ha and 5.93 t/ha, respectively), the study highlights the efficacy of manipulating habitats to enhance biocontrol services in rice fields. By providing nectar sources, alternative prey, and refuges for natural enemies, this approach offers promising prospects for reducing insecticide usage in rice fields by maintaining or potentially increasing rice yield equivalents. Bangladesh Rice J. 27(1): 49-60